On Boundary Value Problems for ϕ-Laplacian on the Semi-Infinite Interval - Lepin, Arnold; Lepin, Leonid; Vasilyev, Nickolay (Mathematical Modelling and Analysis, 2017)
The Dirichlet problem and the problem with functional boundary condition for ϕ-Laplacian on the semi-infinite interval are studied as well as solutions between the lower and upper functions.